It's plain sailing with the trade winds. - North, Michael (Times Higher Education Supplement, 2006)
This article focuses on the significance of linking academic output and business as exhibited by the success of Greenwich University in England. A software was developed by Ed Galea and his research group that focused on the use of computational fluid dynamics programs to help companies and governments in understanding the impact of industrial accidents and disasters. The university posted the strongest growth in income from industry links between 2002 and 2005. Companies that have been sponsoring Greenwich University are identified.